2011
DOI: 10.1258/ar.2011.110268
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of leg-length discrepancy using laser-based ultrasound method

Abstract: The ultrasound-laser technique is quick and easy to perform. Both reliability and agreement with the radiographic method are excellent. The ultrasound measurement is non-invasive and therefore a potential alternative to radiographic methods in the evaluation of LLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
2
11
0
1
Order By: Relevance
“…In the assessment of inter-rater reliability, two physiotherapists from Seinäjoki University of Applied Sciences measured 20 healthy voluntary students with no known previous LLD (90% women, mean age 23 years (range 19–35 years) on two consecutive days, blinded to each other’s assessment. For the evaluation of intra-rater reliability, the same two physiotherapists measured the same 20 voluntary students in mixed order on two consecutive days [12]. The same two physiotherapists measured also the participants of this study but did not participate in the study otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the assessment of inter-rater reliability, two physiotherapists from Seinäjoki University of Applied Sciences measured 20 healthy voluntary students with no known previous LLD (90% women, mean age 23 years (range 19–35 years) on two consecutive days, blinded to each other’s assessment. For the evaluation of intra-rater reliability, the same two physiotherapists measured the same 20 voluntary students in mixed order on two consecutive days [12]. The same two physiotherapists measured also the participants of this study but did not participate in the study otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously established a new LLD measurement with a laser ultrasound range meter [12]. The measurement method showed an almost perfect agreement between repeated measurements with minimal systematic errors.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the previous studies [4-6,10] LLD was assessed using erect-posture radiography, while some [7,8] used even the clinical method, which is less reliable and valid than radiographic or ultrasound methods [15,16]. The strength of our study is the validated accurate method to measure LLD [12]. Our laser-based ultrasound measuring method was accurate and easy to use, which makes it suitable for large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound technique has been reported as reliable when compared to radiographic measurement [11]. Recently, we found that a modified ultrasound method was reliable and its agreement with radiographic method was excellent [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Lasers are commonly used in the medical field for measurement including facial imaging, corneal thickness, and limb length. In these applications, lasers are easy to operate and possess high measurement reliability [ 9 , 10 ]. Although, lasers are not used in the medical field to measure height, veterinarians use laser devices to measure animal height.…”
Section: Introductionmentioning
confidence: 99%